Language issues in comparative education II : policy and practice in multilingual education based on non-dominant languages - Benson, Carol (Associate professor of international and comparative education); Kosonen, Kimmo (Comparative and international education series, 2021)
"This second volume of Language Issues in Comparative Education, following the tradition of the first, introduces the state of the field, re-establishes core terminology and concepts, and situates the chapters in terms of their contributions to multilingual education based on non-dominant languages. The first group of chapters examines language-in-education policy change, applying an innovative framework to analyze diverse contexts including Mozambique, Estonia and the Philippines. The next group of chapters describes activities designed to implement multilingual education. Using examples from Chad, Ethiopia, Kenya and Nepal, they explore progress in teacher professional development and elaboration of materials for literacy and learning through non-dominant languages. Some highlight new areas of the field, attending to speakers of non-dominant languages other than the ones chosen for instruction, and to the urgent multilingual needs of refugee learners. The final group of chapters presents strategies for research and advocacy, illustrated with examples from DR Congo, Uganda and India. Taken together, these contributions form a cohesive body of work that takes stock of advances in multilingual education and moves the field forward. The authors and editors share a common commitment to comparativism in their methods and analysis, and aim to contribute to a more inclusive and multilingual education for all"--